2016
DOI: 10.1080/09205063.2016.1226042
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation optimization of lemon balm antioxidants in calcium alginate hydrogels

Abstract: Calcium alginate hydrogel beads were used to encapsulate lemon balm extract. Chitosan layer was used to investigate the effect of hydrogel coating. To determine the interactions of antioxidant compounds of extract with encapsulation materials and its stability, microstructure of hydrogel beads was thoroughly monitored using scanning electron microscopy and Fourier transform infrared (FTIR). Total polyphenols content and antiradical activity of lemon balm extract were also evaluated before and after encapsulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 23 publications
5
30
0
Order By: Relevance
“…This effect remains true up to a TSP concentration of 1.02 g ml -1 , after that; further, increase in TSP concentration lowers the EE%. A similar phenomenon was observed by previous researchers 8 , where a decline in EE% was noticeable above extract concentration of 1 g ml -1 .…”
Section: Fig 1: 3d Response Surface Graphs Showing the Interaction Esupporting
confidence: 90%
“…This effect remains true up to a TSP concentration of 1.02 g ml -1 , after that; further, increase in TSP concentration lowers the EE%. A similar phenomenon was observed by previous researchers 8 , where a decline in EE% was noticeable above extract concentration of 1 g ml -1 .…”
Section: Fig 1: 3d Response Surface Graphs Showing the Interaction Esupporting
confidence: 90%
“…Sodium alginate hydrogel beads formed by ionic cross-linking with CaCl 2 do not interact with lemon balm extract, and the antioxidant activity of the extract did not change after encapsulation. [32] However, encapsulation efficiency of oil containing drug has been reported to be inversely proportional to the size of alginate-based particles. [26] Encapsulation efficiency is greatly influenced by the degree of cross-linking.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the observed release kinetics of TP was quite prolonged, much lower concentrations of TP have been released from the chitosan‐based edible films in comparison with those based on alginate and pectin, whereby the same trend was observed with the release of AC. Again, a possible explanation of such occurrence could be the formation of strong polyphenol–chitosan complexes (Talón et al , ), as well as a possible higher stability of chitosan in SGF and SIF (Najafi‐Soulari et al , ). These results are in accordance with those obtained by Trifković et al .…”
Section: Resultsmentioning
confidence: 99%
“…Even though the observed release kinetics of TP was quite prolonged, much lower concentrations of TP have been released from the chitosan-based edible films in comparison with those based on alginate and pectin, whereby the same trend was observed with the release of AC. Again, a possible explanation of such occurrence could be the formation of strong polyphenol-chitosan complexes (Tal on et al, 2017), as well as a possible higher stability of chitosan in SGF and SIF (Najafi-Soulari et al, 2016). These results are in accordance with those obtained by Trifkovi c et al (2015), who reported on the lower extent of thymederived hydroxycinnamic acids release from chitosan microbeads, possibly due to the presence of multiple hydroxyl groups in this group of polyphenols, which establish strong hydrogen and covalent bonds with amino groups present in the chitosan molecules.…”
Section: Release Profiles Of Total Polyphenols (Tp) and Acmentioning
confidence: 99%